2019
DOI: 10.1108/itp-06-2017-0198
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Facebook to Instagram migration: a push-pull migration model perspective

Abstract: Purpose Emerging social networking sites (SNSs) are less advantageous than leading SNSs in attracting users. They might stand a better chance if they know what users want. The purpose of this paper is to study factors that urge Facebook users to switch to Instagram to reveal how latecomers in the SNSs circuit can win the hearts of users. Design/methodology/approach This study proposes an SNS switching framework that is adapted from the demographic Push-Pull (PP) migration model to investigate users’ switchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 72 publications
(175 reference statements)
0
29
0
Order By: Relevance
“…This study includes several major contributions. First, from a theoretical perspective, previous switching behavior studies on PPM have tended to discuss long-term-oriented migration behavior, such as switches from Instagram to Facebook (Hou and Shiau, 2020 ), from E-commerce to M-Shopping or social commerce (Chang et al, 2017 ; Li and Ku, 2018 ), or from mobile instant messaging (Sun et al, 2017 ) or cloud storage services (Wu et al, 2017 ; Cheng et al, 2019 ). This study investigated migration behavior during the emergency management implemented by Chinese universities under the impact of the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…This study includes several major contributions. First, from a theoretical perspective, previous switching behavior studies on PPM have tended to discuss long-term-oriented migration behavior, such as switches from Instagram to Facebook (Hou and Shiau, 2020 ), from E-commerce to M-Shopping or social commerce (Chang et al, 2017 ; Li and Ku, 2018 ), or from mobile instant messaging (Sun et al, 2017 ) or cloud storage services (Wu et al, 2017 ; Cheng et al, 2019 ). This study investigated migration behavior during the emergency management implemented by Chinese universities under the impact of the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Push effect includes negative influences that drive users to leave existing services. Moreover, several studies have demonstrated the influence of push effects in switching to a new service (Hou & Shiau, 2020 ; Jung et al, 2017 ; Li & Ku, 2018 ). Learning convenience, quality of service, and security risk have proven to be push-oriented effects in previous studies (Chen & Keng, 2019 ; Cheng et al, 2019 ; Liao et al, 2019 ).…”
Section: Research Methodology and Hypothesesmentioning
confidence: 99%
“…How to think about switching intention from switching classrooms to online learning platforms? Additionally, regarding the switching intentions of the users, previous studies mainly used PPM to explain the switching behavior (Hou & Shiau, 2020 ; Xu et al, 2014 ). Based on Bansal et al ( 2005 ) pointed out, the PPM model structures a list of predictor variables into theoretically defined effect categories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, multicollinearity occurs when there are two constitutes or more variables are highly correlated. Evaluation of multicollinearity can be done by assessing variance inflation factors (VIF) (Hou & Shiau, 2019). If the VIF value is greater than 10 and the tolerance level greater than 0.10, then there is an issue with the multicollinearity (Mayr & Zins, 2012).…”
Section: Normality Analysismentioning
confidence: 99%